O espaço é a flor azul do imaginário: Gaston Bachelard e Walter Benjamin em Paris – a descoberta de uma paisagem literária - Valéria Cristina Pereira da Silva; Carlos Fonseca Clamote Carreto (Confins)
The investigative trajectory of this proposal was to understand the imaginary of the city according to the theoretical and methodological contributions of G. Bachelard’s phenomenology of imagination and W. Benjamin’s concept of montage, how the flanerie and the poetical topology are articulated. We read works from G. Bachelard (1884-1962) and W. Benjamin (1892-1940) that relate to the city of Paris and the way they lived in the city and wrote about it. In an allegorical and phenomenological way, we took the image of the blue flower, as a symbol of the space in the philosophy of the imagination and the imaginary, as well as the survival of the romanticism that belongs to both philosophers. The blue flower is the direct image of the imagination, manifested in the consciousness and also in the desire as a place to be reached, and at the same time, an emblem of an occult dimension, of something that waits to be discovered. The ontology of the space in the imaginary is the central theme of this work whose main objective is to understand the space lived in the literary landscapes as a thematic branch of the city’s imaginary and, above all, to understand the imaginary by showing the relationships that exist in these two theoretical and methodological paths, with their own perspectives and possibilities of development between the studies of Geography and Literature, through the literary landscape that unfolds in the city’s imaginary.